Evidence-Based Information on Mammography Screening in Austria – Reality or More Pie in the Sky? - Rásky, É.; Groth, S. (Das Gesundheitswesen, 2013)
Health literacy is gaining increasing importance in prevention and health care. This is the case for patients and for health-care professionals. Information and risk communication should comply with defined criteria and strengthen health literacy as they are a prerequisite for informed decision making.In this study, we analyse the content of the printed information material (brochures and pamphlets) on mammography screening for consumers that were distributed in Austria in 2011.The evaluation of the 11 brochures shows that the content does not comply with the prerequisites for informed decision making.Since the last study – published in 2004 – the situation has only slightly improved. The authors reemphasise the need for a targeted multimodal information campaign. This is particularly important as a systematic national mammography screening program in compliance with the guidelines of the European Commission will be introduced in Austria in 2013.
Keywords: mammography screening; information material (brochures and pamphlets); informed decision making; health literacy